Técnicas de estudio y rendimiento académico de los y las estudiantes del primer año de la carrera de Educación Básica de la Universidad Técnica de Cotopaxi. diseño de una propuesta alternativa - Núñez Hernández, Edna Evelin (2016)
This researching gets up from concern for the study habits of college students, this is a constant concern in all universities, and it is one of the key elements to improve the quality of higher education. Many researches and solutions have been raised about it, all aimed at the causes and the effects caused by this constant to raise various alternative solutions, however the problem still present in the educational world.